Development of Slow-Release Urea Additives Using Autoclaved Oil Palm Empty Fruit Bunches and Urea via Wet Granulation for Ruminants - Harahap, Rakhmad Perkasa; Tohardi, Ahmad; Prihambodo, Tri Rachmanto; Esesa, Auli Salwa; Tanjung, Melyanti Putri (ANIMAL PRODUCTION, 2025)
This study developed slow-release urea (SRU) additives using autoclaved oil palm empty fruit bunches (OPEFB) and urea via wet granulation to improve nitrogen utilization in ruminants. OPEFB was autoclaved at 121°C and 1 atm pressure to create a stable matrix, which was then combined with urea in different proportions to form SRU. In the first phase, the physical and morphological properties of autoclaved and non-autoclaved OPEFB were analysed using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) spectroscopy. Neutral detergent fibre (NDF) and acid detergent fibre (ADF) were measured, with hemicellulose calculated as the difference between NDF and ADF. In the second phase, SRU formulations included varying percentages of urea and autoclaved OPEFB: SRU 100 (100% urea), SRU 98 (2% OPEFB), SRU 96 (4% OPEFB), SRU 94 (6% OPEFB), SRU 92 (8% OPEFB), and SRU 90 (10% OPEFB). SEM and FTIR descriptively showed surface changes in OPEFB after autoclaving, including increased porosity. Autoclaving also descriptively reduced NDF, ADF, lignin, cellulose, and hemicellulose contents. In vitro rumen incubation revealed that the addition of autoclaved OPEFB in SRU reduced urea release and pH in the rumen at various time intervals: 3, 6, 9, and 24 hours. SRU with autoclaved OPEFB optimizes urea use and controls nitrogen release.